The World Bank’s Dispute Resolution Service: Procedural Reforms to Ensure Meaningful Access to Remedies for Project-Affected People - Brosseau, Jonathan (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2024)
In 2020, the World Bank established the Dispute Resolution Service (DRS) to address complaints from people adversely affected by its projects. The DRS enables them to engage directly with borrower States responsible for project implementation, using mediation, fact-finding, and other methods. As outlined in Section I, this paper examines how the DRS strengthens affected people’s access to remedies and how the DRS should further strengthen such access. Section II presents the standards that underpin the access to a remedy provided by the DRS. Legal standards derive from the Bank’s founding treaty, customary international law, and potential immunities before national courts. Policy standards derive from the Bank’s three remedial mechanisms. First, the 1993 Inspection Panel investigates the Bank’s compliance with its policies, based on three principles: accessibility, effectiveness, and independence. Second, the 2015 Grievance Redress Service facilitates corporate-level dispute resolution. Third, the Bank created the DRS solely to enhance access to remedy through dispute resolution at the organization’s highest level. Section III proposes improvements to the DRS for each principle. Regarding accessibility, the Bank should expand participation opportunities for affected people, including by guaranteeing minimum access to project information. Regarding effectiveness, the Bank should require the “consistency” of dispute resolution agreements with its policies, the default publication of agreements, and mandatory verification of agreement implementation. Regarding independence, the Bank should ensure greater options in sequencing compliance review and dispute resolution processes and introduce concrete measures to mitigate the DRS’ institutional interest in outcomes. Section IV concludes that the DRS’ procedural shortcomings raise doubts about its ability to meaningfully enhance access to remedies, aligning instead with the contemporary trend in international law toward flexible dispute resolution. More broadly, the DRS illustrates the relevance of refining global administrative law theory through a transnational perspective that considers the distinct political, institutional, and economic forces that shape enforcement mechanisms.